THE NEEDS TO LEARN ABDURAUF FITRAT'S TEACHING OF PEDAGOGICAL EDUCATION - Abdujalilova Sh. A. (Galaxy International Interdisciplinary Research Journal, 2022)
The article deals with the study of teacher education by the first Uzbek professor Abdurauf Fitrat.